A STUDY OF MARINE CSEM SURVEY GEOMETRY FOR SEABED LOGGING - HUSSAIN, NAZABAT HUSSAIN (2011)
In recent years marine Controlled Source Electromagnetic (CSEM) method is being used for hydrocarbon exploration in deeper water. The marine CSEM is preferred over seismic due to its ability to differentiate reservoir of resistive hydrocarbon and conductive saline fluids. In marine CSEM method, however, the survey data is highly dependent on source-receiver position and orientation. Furthermore, real geological conditions are extremely varied and it is rarely possible to turn the survey data into reliable picture of geological structure using virtual simulation. Consequently, it is important to understand EM field behavior for various geological models and source-receiver position to improve virtual simulation process. The aforementioned aspect studied through comprehensive forward modeling is an alternate to real time geophysical surveys. In this research, a forward modeling algorithm is employed as a staggered-grid finite difference solution to the totalelectric field Maxwell’s equations. Solution are achieved through (i) an optimal grid technique that extends the boundaries of the mesh outward from the region of interest using a minimal number of nodes, and (ii) a direct matrix solution technique that allows for simultaneous solution for all sources. The forward modeling algorithm is applied on 1D and 2D geological models implemented using MATLAB. Results obtained provide qualitative understanding of electromagnetic signal propagation through different stratified media with various source positions and orientation. 1D forward modeling is used to find optimal frequency for specific depth and for studying effects of speed variation of dipole source. The 2D forward modeling is used to understand EM field behavior for resistive hydrocarbon and conductive saline fluid reservoirs. Furthermore, inaccuracy due to improper survey geometry such as dipping effect is also analyzed and discussed. In essence, forward modeling was applied to various scenarios and obtained results were accurately matched with previously published work of real time survey. This is a significant step towards the improvement in confidence modeling which in turn can potentially help to reduce surveying cost.